Statistical Optimization of Green Synthesized Silver Nanoparticles Using Syzygium cumini Leaf Extract through Central Composite Design and Antidiabetic Applications - Veeranna S. Hombalimath (Asian Journal of Pharmaceutics (AJP), 2025)
Aims: This study reports the eco-friendly synthesis of silver nanoparticles (AgNPs) using Syzygium cumini leaf extract under a range of pH conditions (3–9), with optimal nanoparticle formation observed at pH 9 as evidenced by ultraviolet-visible spectroscopy. Materials and Methods: Comprehensive characterization techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR), were employed to elucidate the properties of the synthesized AgNPs. Results and Discussion: XRD analysis confirmed the crystalline nature of the nanoparticles, revealing an average size of 21.63 nm, while SEM imaging demonstrated predominantly spherical morphologies with occasional aggregation. FTIR studies identified key functional groups from the leaf extract involved in nanoparticle stabilization. The synthesis process was further optimized using response surface methodology with a central composite design, which identified silver nitrate concentration as a critical parameter. Notably, the synthesized AgNPs exhibited significant concentrationdependent anti-diabetic activity, achieving approximately 43% enzyme inhibition at 150 µg/mL, likely due to interactions with α-amylase or α-glycosidase that modulate glucose metabolism. Conclusion: These results underscore the promising biomedical potential of green-synthesized AgNPs, particularly for diabetes management, and highlight the advancement of sustainable nanotechnology approaches.